Tokoh-Tokoh Dalam Penjara Bahasa - Endin Saparudin; Arip Senjaya; Alfi Bahaviani (Jurnal Inovasi dan Kreativitas (JIKa), 2022)
Problem: In an interview in 2004, female writer Linda Christanty admitted that she had used politics as the initial foundation of her writing career. Furthermore, for Christanty, writing both literature and journalism is not only a celebration of pleasure, but also her choice and opportunity to take action. Unfortunately, in Christanty’s three published anthologies of short stories, namely Kuda Terbang Maria Pinto (2004), Rahasia Selma (2010), and Seekor Anjing Mati di Bala Murghab (2012), the politics turns out to be neither a dominant nor an explicit theme. Christanty appears to “merely” hands out the theme of politics as a story filler which is barely alluded while putting more emphasis on inter-relationships among human beings (the characters within her short stories). In fact, the majority of Christanty’s short stories’ protagonists often seem to try to take a form of identity that is acceptable to their social surroundings. Purpose: this writing will attempt to examine the desires of the three anthologies’ protagonists while also proving that these characters have experienced symbolic violence as they have been linguistically repressed. Methodology: Hence, using Lacanian Psychoanalysis, this writing will attempt to examine the desires of the three anthologies’ protagonists while also proving that these characters have experienced symbolic violence as they have been linguistically repressed. Consequently, the protagonists of Christanty’s short stories always find themselves in a constant tension between the Symbolic and the Real. Results/Finding: Furthermore, this evidences that these protagonists are perpetually trapped in linguistic confinement, which ends up in forming chains of significations to the Imaginary. These characters have been eternally cursed to desire slippery linguistic signifiers as they have been anchored by Name-of-the-Father (Nom du Pere) through the socio-cultural order that influences the characters themselves. Paper Type: Literature studies Keywords: short stories, Linda Christanty, Lacanian Psychoanalysis, Linguistic Confinement